2008
DOI: 10.1111/j.1365-313x.2008.03473.x
|View full text |Cite
|
Sign up to set email alerts
|

A male sterility‐associated mitochondrial protein in wild beets causes pollen disruption in transgenic plants

Abstract: SummaryIn higher plants, male reproductive (pollen) development is known to be disrupted in a class of mitochondrial mutants termed cytoplasmic male sterility (CMS) mutants. Despite the increase in knowledge regarding CMSencoding genes and their expression, definitive evidence that CMS-associated proteins actually cause pollen disruption is not yet available in most cases. Here we compare the translation products of mitochondria between the normal fertile cytoplasm and the male-sterile I-12CMS(3) cytoplasm der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 29 publications
3
67
0
Order By: Relevance
“…Several transformants containing orf gene constructs, with or without a mitochondrial targeting sequence, exhibited a semi-sterile or male sterile phenotype (He et al 1996;Wang et al 2006;Kim et al 2007;Yamamoto et al 2008). The failure of mitochondrial expression of novel orfs to induce male sterility is probably due to problems in disruption of mitochondrial membranes (Rhoads et al 1995;He et al 1996), effect on ATP synthase function (Bergman et al 2000;Sabar et al 2003) and pollen abortion by programmed cell death in transgenic plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several transformants containing orf gene constructs, with or without a mitochondrial targeting sequence, exhibited a semi-sterile or male sterile phenotype (He et al 1996;Wang et al 2006;Kim et al 2007;Yamamoto et al 2008). The failure of mitochondrial expression of novel orfs to induce male sterility is probably due to problems in disruption of mitochondrial membranes (Rhoads et al 1995;He et al 1996), effect on ATP synthase function (Bergman et al 2000;Sabar et al 2003) and pollen abortion by programmed cell death in transgenic plants.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally considered that CMS is caused by the rearrangement of mitochondrial genomes, which, in many cases, is attributed to the generation of novel Open Reading Frames (ORF) (Yang and Zhang 2007). In a number of cases, transcripts originating from these altered open reading frames are translated into unique proteins that appear to interfere with mitochondrial function and pollen development (Yamamoto 2008). CMS anther degeneration is probably caused by dysfunction of tapetum or vacuolation of tapetum, PMCs, and microspores (Shi et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…After introducing the BT-rice orf79 gene into Taichung 65 carrying normal cytoplasm, it is revealed that ORF79 is toxic to plant regeneration when expresses as a fusion with mitochondrial targeting sequence of the ATPase subunit [11]. The CMS-associated mitochondrial protein in petunia, ORF129 results in male sterility in transgenic tobacco plants [12]. It is reported that the expression of sunflower cytoplasmic male sterilityassociated open reading frame, orfH522 induces male sterility in transgenic tobacco plants [13].…”
Section: Cms-associated Chimeric Orfs Are Often Toxicmentioning
confidence: 99%
“…However, as is the case with rice COX11 and other CMS systems, the mode of action may affect more than one category. An additional interesting dimension is that while the expression of CMS genes does not appear to be restricted to the male reproductive tissues in many species (Warmke and Lee, 1978;Abad et al, 1995;Yamamoto et al, 2008;Chen and Liu, 2014), accumulation of CMS-related proteins can be highly spatiotemporally specific to induce CMS (Abad et al, 1995;Wang et al, 2006;Luo et al, 2013).…”
Section: And [4]mentioning
confidence: 99%